Extracorporeal Membrane Oxygenation for COVID-19: Updated 2021 Guidelines from the Extracorporeal Life Support Organization. Issue 5 (May 2021) - Badulak, Jenelle; Antonini, M. Velia; Stead, Christine M.; Shekerdemian, Lara; Raman, Lakshmi; Paden, Matthew L.; Agerstrand, Cara; Bartlett, Robert H.; Barrett, Nicholas; Combes, Alain; Lorusso, Roberto; Mueller, Thomas; et al.
Abstract : Disclaimer: This is an updated guideline from the Extracorporeal Life Support Organization (ELSO) for the role of extracorporeal membrane oxygenation (ECMO) for patients with severe cardiopulmonary failure due to coronavirus disease 2019 (COVID-19). The great majority of COVID-19 patients (>90%) requiring ECMO have been supported using venovenous (V-V) ECMO for acute respiratory distress syndrome (ARDS). While COVID-19 ECMO run duration may be longer than in non-COVID-19 ECMO patients, published mortality appears to be similar between the two groups. However, data collection is ongoing, and there is a signal that overall mortality may be increasing. Conventional selection criteria for COVID-19–related ECMO should be used; however, when resources become more constrained during a pandemic, more stringent contraindications should be implemented. Formation of regional ECMO referral networks may facilitate communication, resource sharing, expedited patient referral, and mobile ECMO retrieval. There are no data to suggest deviation from conventional ECMO device or patient management when applying ECMO for COVID-19 patients. Rarely, children may require ECMO support for COVID-19–related ARDS, myocarditis, or multisystem inflammatory syndrome in children (MIS-C); conventional selection criteria and management practices should be the standard. We strongly encourage participation in data submission to investigate the optimal use of ECMO for COVID-19.